Etika Ekosentrisme sebagai Paradigma Pengelolaan Sumber Daya Alam dan Lahan Berkelanjutan di Indonesia - Rofifah Aulia Amanda; Muhammad Sarjan (Mataram University, 2026)
Global environmental crises such as land degradation, deforestation, pollution, biodiversity loss, and climate change show that anthropocentric-oriented natural resource management hasnot been able to create environmental sustainability. Indonesia as a megabiodiversity country also faces serious environmental problems, such as the area of degraded land reaching 24.3-48.3 million hectares, the rate of net deforestation of 175.4 thousand hectares per year, and the decline in soil biodiversity on intensive agricultural land. This condition shows the need for an alternative paradigm that pays more attention to ecological sustainability. This research aims to analyze the ethics of ecocentrism as a paradigm of sustainable natural resource and land management in Indonesia, identify its main principles, examine its implementation in environmental management, and formulate sustainable development policy recommendations. The research uses a literature review method with a descriptive quantitative analysis approach. Data is obtained from scientific articles, government reports, and international documents relevant to sustainable environmental management. A total of 78 articles and documents were analyzed in depth. The results of the study show that the ethics of ecocentrism places nature as an entity that has intrinsic value and is applied through agroforestry strategies, soil and water conservation, forest rehabilitation, and local community empowerment. In addition, the integration of sustainable development principles in national policies such as the SDGs and FOLU Net Sink 2030 shows a shift towards more ecologically oriented environmental management. However, its implementation still faces challenges in the form of low environmental awareness, limited funding, and conflicts of interest between natural resource exploitation and environmental conservation. However, the ethics of ecocentrism can be a relevant alternative paradigm in the sustainable management of natural resources and land in Indonesia because it is able to encourage a balance between human needs and environmental sustainability. Therefore, it is necessary to strengthen ecosystem-based policies, increase environmental education, support funding, and cooperation between the government, the community, academics, and the private sector to support the implementation of sustainable environmental management.